Profile Number of Mice Takizoit after Treatment With Alkaloid Fraction of Alstonia scholaris Leaves - Hakim, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The prevalence of toxoplasmosis in Indonesia at 2006 was 43-88%. Drugs that have been the most widely used for the treatment of patients with toxoplasmosis include pyrimethamine and spiramicin. However, these drugs have been reported to cause side effects such as bone marrow suppression, penetrate the blood brain barrier, crossed the placenta and fetal blood. Therefore necessary to find alternative drugs for toxoplasmosis effective and safe. This research studied the effect of alkaloid fraction of leaves of plants Alstonia scholaris to the number takizoit profiles in intraperitoneal fluid of mice infected with Toxoplasma gondii. This research used the experimental animals were grouped as the control group and the treatment group. In the treatment group, each group was given treatment with fraction extract alkaloids from leaves of plants Pulai. The results showed the number takizoit mice infected with Toxoplasma gondii parasites without therapy is 957.5 x 103 whereas the alkaloid fraction of the ethanol extract of leaves is 737.5 x 103.Â Keywords: Leaves of Pulai (Alstonia scholaris), Toxoplasma gondii, toxoplasmosis.